Efficacy and Safety of Hydroquinone, Kojic Acid and Glycolic Acid Combination in the Treatment of Melasma (Bangladesh Journal of Medical Science, 2012)
Background & Methodology: It was an opened clinical trial. The study was carried out from March 2009 to February 2011, in the outpatient department of Dermatology and Venereology, Bangabandhu Sheikh      Mujib Medical University (BSMMU) Dhaka, Bangladesh to evaluate the efficacy and side effects of the combination therapy of hydroquinone(HQ), kojic acid(KA) and glycolic acid(GA) for the treatment of melasma. Patients suffering from melasma were selected as study population. Within the period of data collection, thirty patients of melasma were assigned purposively. The efficacy was evaluated using Melasma Area and Severity Index (MASI) Score. The severity of melasma of each of the four regions (forehead, right malar region, left malar region and chin) are assessed based on three variables, percentage of the total area involved (A), darkness (D) and homogenicity (H).Results:The study showed that majority (30%) of the cases were between 20 to 25 years, majority (77%) of patients were female, (50%) patients were housewives, (50%) were in graduation level of education, (50%) of patients was found as upper class and negative family history was present in majority (80%) of cases. It was seen that highest (93%) number of patients were malar type and 7% were centro-facial type. The study showed the change in MASI Score after treatment with combination therapy (GA 2%, HQ 2% and KA 1%). After 12 weeks of treatment, the average MASI score was decreased by 24.20% indicating mild reduction of the severity of melasma and 18%, 18%, 9% and 55% patients developed side -effects like itching, burning sensation, scaling, and erythema respectively. Conclusion: Combination therapy (GA 2%, HQ 2% and KA 1%) has a few lightening effect on melasma, with no remarkable side effects. Further study should be conducted with large number of sample and longer follow up. DOI: http://dx.doi.org/10.3329/bjms.v11i3.11720 Bangladesh Journal of Medical Science Vol. 11 No. 03 July12